Analysis of the Character of Hard Work in Thematic Learning in Elementary Schools - Nursakinah; Fadillah, Putri; Irma Widya Ningsih; Junaidi, Junaidi (Journal Evaluation in Education (JEE), 2022)
Research objectives: This study aims to find out how thematic learning can become meaningful for students and the thematic learning outcomes of third-grade elementary school students.Methodology: This research is qualitative research. By using a case study design. The research subjects were the educators who were observed and 10 students in grade III elementary schools who were obtained using a purposive sampling technique.Main findings: Thematic learning in elementary schools has strengths and increases students' hard work in learning.Novelty/Originality of this study: Thematic learning is able to provide improvement and positive influence in all learning components